SIMULINK SOFTWARE FEATURES FOR MODELLING A SMALL-SIZE LOADER - Yefymenko, O.; Hrichchina, A.; Єфименко, О. В.; Гріччіна, А. В.; Ефименко, А. В.; Гриччина, А. В. (Харьковский национальный автомобильно-дорожный университет, 2017)
Computer simulation as a tool to determine the loading for implements and hydraulic drives of small-size loaders has been considered in the paper. A number of lifting mechanism design models has been built; their strengths and shortcomings have been analysed. It has been proposed to alter the machine’s hydraulic drive design as well as to redesign the arm and the levelling mechanism to improve reliability of a small-size loader.
ОСОБЛИВОСТІ ВИКОРИСТАННЯ SIMULINK ДЛЯ МОДЕЛЮВАННЯ МАЛОГАБАРИТНОГО НАВАНТАЖУВАЧА
ОСОБЕННОСТИ ИСПОЛЬЗОВАНИЯ SIMULINK ДЛЯ МОДЕЛИРОВАНИЯ МАЛОГАБАРИТНОГО ПОГРУЗЧИКА
Keywords: small-size loader; computer simulation of road-building machines; analysis; arm; pump capacity; малогабаритний навантажувач; комп’ютерне моделювання БДМ; аналіз; стріла; продуктивність насоса; малогабаритный погрузчик; компьютерное моделирование СДМ; анализ; стрела; производительность насоса; 681.5.015:658.786